2007
DOI: 10.1080/08860220601166222
|View full text |Cite
|
Sign up to set email alerts
|

Iloprost for Additional Anticoagulation in Continuous Renal Replacement Therapy—A Pilot Study

Abstract: Purpose. The aim of this pilot study was to compare the effect of heparin anticoagulation with and without iloprost administration during continuous renal replacement therapy (CRRT) in critically ill patients. Material and methods. In a prospective, randomized, controlled pilot study at an intensive care unit at a university hospital, 20 patients requiring CRRT were investigated. Patients were allocated into two groups: group 1, the heparin group; and group 2, the heparin plus 1 ng/kg/min iloprost. In both gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…However, the observed rates of re‐laparotomies because of bleeding or intra‐abdominal hematoma were comparable in both our groups. Therefore, an increased risk of bleeding complications under iloprost treatment cannot be assumed (50, 51).…”
Section: Discussionmentioning
confidence: 99%
“…However, the observed rates of re‐laparotomies because of bleeding or intra‐abdominal hematoma were comparable in both our groups. Therefore, an increased risk of bleeding complications under iloprost treatment cannot be assumed (50, 51).…”
Section: Discussionmentioning
confidence: 99%
“…A few small trials showed improved filter survival during CRRT when adding prostaglandins to heparin compared with heparin alone [95-97]. However, prostaglandins appear to have a limited efficacy when used alone, induce systemic hypotension [98,99], and are expensive.…”
Section: Recommendations and Rationalementioning
confidence: 99%
“…594, 595, 596 A few small trials showed improved filter survival during CRRT when adding prostaglandins to heparin compared to heparin alone. 622, 623, 624 However, prostaglandins appear to have a limited efficacy when used alone, induce systemic hypotension, 625, 626 and are expensive. Their use during CRRT can therefore not be recommended.…”
Section: Rationalementioning
confidence: 99%